Induction of triploidy in turbot (Scophthalmus maximus) does not affect gross body morphology and skeleton characteristics - Hernández-Urcera, Jorge (2019)
Triploid turbot (Scophthalmus maximus) produced by cold shock showed no differences in their gross body morphology and skeleton characteristics compared with their diploid full-sibs.